Factors associated with induced second trimester abortion at a tertiary level hospital of Uttarakhand region: a 6-year retrospective study - Nimonkar, Shweta; Chaudhari, Priyanka; Gupta, Vineeta; Saxena, Namrata; Agarwal, Shivangi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Despite the liberalization of the abortion services since the early 1970s in India, access to safe abortion services remains limited for the vast majority of Indian women particularly from rural areas. Second trimester abortions have different indications and associated with increased maternal morbidity and mortality as compared to the first trimester abortions. Methods: This study was a retrospective study conducted from the January 2014 to December 2019 at obstetrics and genecology department of Shri Guru Ram Rai Institute of Medical and Health Sciences, Dehradun, Uttarakhand, India. All patients of 12 weeks to 20 weeks of confirmed gestational age were given medical method of second trimester abortion. Data was collected and analyzed regarding demographic features, gestational age, indications, and induction-abortion interval and post abortion contraceptive methods accepted by patient. Results: During this study period a total of 180 patients had second trimester abortion at study institute. Maximum number of patients 69 (38.3%) were of 25-30 years of age group and 161 (85%) patients were of Hindu religion. Major indication was failure of contraception (42.8%) and congenital anomalies in the fetus (45.6%). There was one case of failed medical abortion in which emergency hysterectomy was done for undiagnosed adherent placenta. All patients were compliant of using contraceptive methods after the abortion because of recent medical and mental stress and majority 82 (45.6%) of the patients preferred oral combined contraceptive pills. Conclusions: Apart from congenital anomalies rest all indications can be reduced if women in our country are empowered to control their fertility, get education to become more aware and provided with social security.